INFORMATION SECURITY AND SAFETY IN CYBERPARKS (Global Journal of Advanced Engineering Technologies and Sciences, 2015)
This paper discusses information security and safety issues in public open spaces. Public open spaces may include high streets, street markets, shopping centres, community gardens, parks, and playgrounds, each of which plays a vital role in the social, cultural and economic life of a community. In this paper we introduce the term CyberPark, which refers to an outdoor public place mashed-up with various ICT tools. Security and safety in public places may include video surveillance of movement and the securing of information and location based service. In this paper, we provide an overview of secured information in communications between user end devices and service providers.